Surface acoustic wave sensor for formaldehyde gas detection using the multi-source spray-deposited graphene/PMMA composite film - Wang, Beibei; Zhou, Lingling; Wang, Xiaoqian (Frontiers in Materials, 2023)
A surface acoustic wave (SAW) formaldehyde sensor based on a graphene/polymethyl methacrylate (PMMA) composite film with high sensitivity and short response and recovery times was proposed in this study. Using a novel multi-source spray deposition method, graphene sheets were uniformly dispersed in a PMMA film to fabricate sensitive films with a three-dimensional framework structure for use in SAW devices. The formaldehyde-sensing ability was enhanced by optimizing the film thickness and operating temperature. The highest performance was achieved for a graphene/PPMA film thickness of 2.2 µm at a temperature of 120 °C.